ILLITE-SMECTITE MIXED-LAYER MINERALS IN THE HYDROTHERMAL ALTERATION OF VOLCANIC ROCKS: II. ONE-DIMENSIONAL HRTEM STRUCTURE IMAGES AND FORMATION MECHANISMS - Murakami T.; Inoue A.; Lanson B.; Meunier A.; Beaufort D. (My University, 2005)
Smectite illitization was investigated in felsic volcaniclastic rocks from a drill core near the Kakkonda active geothermal system, Japan, using high resolution transmission electron microscopy (HRTEM) that provided one-dimensional structure images of mixed-layer illite-smectite (I-S) minerals normal to [hk0]. Simulated images of a rectorite-like structure revealed that smectite can be distinguished from illite in mixed-layer I-S by HRTEM if the basal spacing of smectite is larger than that of illite. The larger basal spacing of smectite, 1.3 nm under HRTEM, was obtained by intercalation of dodecylammonium ions into smectitic interlayers. In simulated and observed images normal to [hk0], tetrahedral (T) and octahedral (O) cation-layers are imaged as dark lines, an illitic interlayer a bright line, and a smectitic interlayer a dark line sandwiched by two bright lines. Samples are from 435 m (5% I; R0), 635 m (35% I; R0), 656 m (62% I; R1), and 756 m (85% I; R3) depths where % I is the percent of illite layers in a sample and R is the Reichweite parameter. Sample 435 consisted mostly of smectite, and illite layers occurred, though small in amount, as M1 units (module of type 1, defined as one consisting of two polar T-O-T silicate layers with one central illitic interlayer and two, half smectitic interlayers at the outermost surface; the number corresponds to that of central illitic interlayers). M1 units were dominant and isolated or consecutive smectite layers of > two were present in sample 635. Sample 656 consisted mostly of packets of M1 units of 1 to 5 containing M2 to M5 units occasionally. Isolated or consecutive smectite layers of > two were not present in 656. Illite layers occurred almost as M1 units in samples 435, 635 and 656, and the number of M1 units increased with increase in % I. Sample 756 was characterized by the presence of M2 to M10 units accompanied by smectitic interlayers at the external surface and the absence of M1 units and isolated smectite layers. HRTEM data strongly suggest that illitization in a hydrothermal system occurs by precipitation of M1 units for mixed-layer I-S minerals up to 60% I. This does not require the presence of precursor smectite. Illitization of I-S minerals with more than 60% I proceeds by precipitation of various types of Mn(n≥2) units. Illite occurs only as Mn(n≥1) units throughout illitization.
Keywords: Alkylammonium solvation; HRTEM; Hydrothermal system; Illite-smectite mixed-layer minerals; Structure image